2023
DOI: 10.7717/peerj.14244
|View full text |Cite
|
Sign up to set email alerts
|

Change in eating habits during the Spanish COVID-19 pandemic lockdown: evidence for a sample of university community

Abstract: Background The stress and anxiety caused by COVID-19 lockdown may have changed the eating habits of the population. Our aim is to assess the eating changes that have taken place due to the pandemic. Methods Data were collected through an electronic survey created by the Health Economics Research Group of the University of Cantabria and IDIVAL and conducted between 14/01/2021 and 19/02/2021. A total of 1,417 responses were recorded, but only 507 complete observations were considered. We carried out a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…In the same line, other studies have reported that the positive changes in eating habits observed during the months of lockdown (eating fresh foods, fruits, vegetables, dairy products, etc.) were significantly associated with higher income, a better self-perceived health state and better sport habits [63], more time available for cooking [55], and simply eating at home [64]. Another study in a sample of adolescents with chronic affectations showed changes in eating habits, with a decrease in the consumption of precooked foods and an increase in homemade food [65].…”
Section: Discussionmentioning
confidence: 97%
“…In the same line, other studies have reported that the positive changes in eating habits observed during the months of lockdown (eating fresh foods, fruits, vegetables, dairy products, etc.) were significantly associated with higher income, a better self-perceived health state and better sport habits [63], more time available for cooking [55], and simply eating at home [64]. Another study in a sample of adolescents with chronic affectations showed changes in eating habits, with a decrease in the consumption of precooked foods and an increase in homemade food [65].…”
Section: Discussionmentioning
confidence: 97%
“…Además, es de destacar el shock que supuso la pandemia de la COVID-19, no solo en términos de mortalidad anticipada sino también en la propia vida de las personas afectando notablemente a su bienestar físico y mental (Odriozola-González et al, 2020;Garvey et al, 2021;Leco-Berrocal et al, 2021;Marques et al, 2021;Padrón et al, 2021;Rodríguez-Larrad et al, 2021;Roldán-Merino et al, 2022) e incluso modificando sus estilos de vida (Imaz-Aramburu et al, 2021;García-Campanario et al, 2022;Ruiz-Zaldibar et al, 2022;Cantarero Prieto et al, 2023). También, llegó lógicamente a afectar al propio devenir de la docencia universitaria (Ożadowicz, 2020;Bustamante et al, 2022;Echeverría, Pozo y Cabellos, 2022;Lera-Torres, Cantarero-Prieto y Pascual-Sáez, 2022;Paños-Castro, Arruti and Korres, 2022).…”
Section: Introducción Y Revisión De Literaturaunclassified